THE ORIGINALITY OF THE ORCHESTRAL STYLE OF N. RIMSKY-KORSAKOV’S OPERA-BALLET MLADA - BORODAVKIN SERGHEI (Studiul Artelor şi Culturologie: Istorie, Teorie, Practică, 2015)
The paper deals with the orchestra style of a little studied but very interesting opera by Rimsky-Korsakov „Mlada”. The work was written under the influence of R Wagner’s opera”Ring of the Nibelung” but at the same time contrasting it and preserving its own identity in the field of orchestra writing as well. As a result, the opera’s orchestra style reveals bright novelty features in Russian music, however not breaking away from its traditions but creatively continuing and enriching them.